Neonatal screening in Spain and cost–effectiveness. (September 2015) - Serrano-Aguilar, Pedro; Castilla-Rodríguez, Iván; Vallejo-Torres, Laura; Valcárcel-Nazco, Cristina; García-Pérez, Lidia
<x xml:space="preserve">Abstract</x> Newborn screening (NBS) programs are subject to inter- and intra-country variations, especially after the introduction of tandem mass spectrometry (MS/MS). Access to MS/MS and variations in interpretation of available evidence seem to explain these differences. Cost considerations have had a minor role on funding decisions given the low direct costs to screen an additional disorder by MS/MS and their low frequency. In order to reduce the wide inter-regional observed variations in NBS in Spain, the Ministry of Health supported by the Spanish Network for Health Technology Assessment developed an evidence-based policy decision process guided by a series of effectiveness and cost–effectiveness reports.